Impact of thymoquinone on the Nrf2/HO-1 and MAPK/NF-κB axis in mitigating 5-fluorouracil-induced acute kidney injury in vivo - Rashid, Summya (Frontiers in Oncology, 2025)
BackgroundChemotherapy-induced organ toxicity is one of the most common toxic effects of 5-fluorouracil (5-FU) in cancer patients. Therefore, new strategies are needed to prevent chemotherapy-induced kidney toxicity. Thymoquinone (TQ), a constituent of the plant Nigella sativa from the family Renunculaceae, has been found to be antiapoptotic, antioxidant, antimicrobial, anti-inflammatory, and protective against renal damage. This study aims to evaluate the effect of TQ in preventing nephrotoxicity induced by 5-FU treatment.MethodMale albino Wistar rats were divided into four groups and administered saline (group I), 5-FU (150 mg/kg; group II), 5-FU+TQ (50 mg/kg; group III), and 5-FU+TQ (100 mg/kg; group IV). On the 21st day, rats were killed, and biochemical, histological, serological, and molecular analyses were conducted using kidney tissues and blood samples.Results5-FU induced kidney injury, as evidenced by alterations in kidney function markers (BUN, Cr, LDH, KIM-1), lipid peroxidation (LPO), ROS generation, histological changes, and a reduction in antioxidant defense mechanism (GSH, GR, GPx, and CAT). Additionally, 5-FU triggered crosstalk between Nrf2 and NF-κB/p38MAPK axis by significantly upregulating p-p38, p-JNK, p-ERK1/2, p-NF-κB, TNF-α, IL-1β, TGF-β, and IL-6, while downregulating Nrf2 and HO-1, resulting in kidney damage. Pre-, post-, and cotreatment with TQ alleviated kidney injury by replenishing antioxidant reserves, reducing serum toxicity, decreasing ROS generation and lipid peroxidation, downregulating p38 MAPK/NF-κB axis/pathway proteins, and upregulating Nrf2 and HO-1, thereby enhancing antioxidant axis and restoring kidney architecture.ConclusionBased on the results obtained in the present study, TQ appears to be a beneficial agent that could be used as an adjuvant therapy for the prevention of 5-FU-induced nephrotoxicity.